Comparison of the Efficacy and Safety Endpoints of Five Therapies for Atrial Fibrillation: A Network Meta-Analysis - Wang, Tongyu; Fang, Tingting; Cheng, Zeyi (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Atrial fibrillation (AF) is a prevalent arrhythmia that occurs in 2%–4% adults and poses a threat to human health. Thus, comparison of the efficacy and safety of therapies for AF is warranted. Here, we used network analysis to compare efficacy and safety endpoints (arrhythmia recurrence, rehospitalization, all-cause mortality, and cardiovascular mortality) among five major therapies for AF. Methods: The PubMed, Cochrane, and Embase databases were searched and relevant literature retrieved. Only studies that made comparisons among the therapies of interest and involved patients with AF were included. Pairwise comparisons and frequentist method (SUCRA plot) analyses were conducted. Results: In total, 62 studies were included in the pooled analysis. In pairwise comparisons, atrioventricular nodal ablation plus permanent pacemaker (AVN+PPM) was associated with a significantly higher risk of atrial arrhythmia recurrence than surgery ablation (odds ratio (OR): 23.82, 95% confidence interval (CI): 1.97–287.59, fixed-effect model; 3.82, 95% CI: 1.01–559.74, random-effects model). Further, radio-frequency ablation was associated with a significantly lower risk of cardiovascular mortality than medication in pairwise comparison (OR: 0.49, 95% CI: 0.29–0.83, fixed-effect model; OR: 0.49, 95% CI: 0.27–0.9, random-effects model). Frequentist analysis indicated that AVN+PPM had the best performance in reducing the risk of safety and efficacy endpoints. Conclusion: Non-pharmaceutical therapies showed superior performance to traditional drug therapy in lowering the risk of safety and efficiency end point events. AVN+PPM performed best in reducing the risk of safety and efficacy endpoints.